Molecular structure, spectroscopic characterization, HOMO and LUMO analysis of PU and PCL grafted onto PEMA-co-PHEMA with DFT quantum chemical calculations - Demir, Pinar; Akman, Feride (Elsevier, 2017)
A newly synthesized polycaprolactone (PCL) and polyurethane (PU) polymers, which grafted onto poly (ethylmethacrylate-co-2-hydroxyethyl methacrylate) (PEMA-co-PHEMA) were characterized both theoretically and experimentally. The FTIR and H-1 NMR spectra were recorded for the PCL and PU polymers and the experimental values were compared the theoretical values. The molecular structure evaluation, vibrational frequencies and 1H NMR chemical shift values, which carried out by using gauge including atomic orbital (GIAO) approach, of the PCL and PU polymers were calculated by using density functional method (DFT/B3LYP) with 6-311G (d, p) as a basis set in the ground state. The calculated data such as vibrational frequencies and chemical shift values show good agreement with experimental values. Besides, the thermodynamic properties such as rotational temperatures, rotational constants, zero-point vibrational energy, specific heat capacity, thermal energy, entropy, enthalpy, the electronic properties such as HOMO and LUMO energies, and molecular electrostatic potential (MEP) surfaces for the PCL and PU were calculated and interpreted. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: PCL; PU; Thermodynamic properties; DFF; HOMO-LUMO; MEP